Concomitant Aorto-axillary Bypass and Beating Heart Total Arterial Coronary Artery Bypass Grafting by RIMA-LIMA Y graft (Cardiovascular Journal, 2013)
In common practice, left internal mammary artery (LIMA) along with great saphanous vein is used in coronary artery bypass grafting (CABG). Day by day total arterial CABG specially use of bilateral mammary arteries are becoming demanding. Coexisting occlusive disease may rarely affect coronary arteries along with left subclavian artery. We have reported a successful concomitant aorto-axillary bypass and CABG of a 52-year-aged man with the diagnosis of triple-vessel-disease (TVD) angiographically along with proximal stenosis in left subclavian artery. Aorto-axillary (left) bypass was done with 6-mm ring re-inforced polytetrafluoroethane (PTFE) graft and CABG was done by total arterial RIMA-LIMA Y graft on beating heart. The post-operative course was uneventful with reappearance of peripheral pulses in left upper extremity. The patient was discharged on the 9th post-operative day. DOI: http://dx.doi.org/10.3329/cardio.v5i2.14325 Cardiovasc. j. 2013; 5(2): 201-205